Prevalence of carriage of extended-spectrum β-lactamase-producing enterobacteria and associated factors in a French hospital. (December 2018) - Jolivet, S.; Vaillant, L.; Poncin, T.; Lolom, I.; Gaudonnet, Y.; Rondinaud, E.; Bendjelloul, G.; Lomont, A.; Lucet, J.-C.; Armand-Lefèvre, L.
Abstract: Objectives: Our aim was to evaluate the prevalence and associated factors for carriage of extended-spectrum β-lactamase-producing enterobacteria (ESBL-PE) in a healthcare facility. Methods: In 2016 a serial cross-sectional survey of ESBL-PE carriage in a French university hospital was conducted. All patients present on the day of the survey were screened for ESBL-PE carriage. Demographic characteristics and risk factors for ESBL-PE carriage were collected. Results: In all, 146/844 patients (17%) were digestive carriers of ESBL-PE; of these, 96 (66%) had not previously been identified. Among patients carrying ESBL-PE, Escherichia coli (62%) and CTX-M type (94%) predominated. Greater age, recent travel abroad, receipt of antibiotic, and prolonged hospitalization were associated with ESBL-PE carriage. Conclusion: Given the high prevalence of ESBL-PE and the high proportion of unknown carriers, our results strongly suggest reinforcing standard precautions rather than contact precautions for controlling the spread of ESBL-PE.